The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/life11101086
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor (rs1137101) and Brain-Derived Neurotrophic Factor (rs925946) Gene Variants Are Associated with Obesity in the Early- but Not in the Late-Onset Population of Hungarian Psoriatic Patients

Abstract: Background: Psoriatic patients have considerably higher odds of being obese compared with the general population; however, the exact pathophysiological link between psoriasis and obesity needs to be elucidated. Methods: To investigate the association of psoriasis with established obesity-related gene variants, we conducted a population-based case-control study including 3541 subjects (574 psoriasis cases and 2967 controls from the general Hungarian population). Genotyping of 20 SNPs at ADIPOQ, BDNF, FTO, GNPDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Kim et al demonstrated that individuals with a BMI of 30 units had a considerably higher risk of psoriasis than those with a BMI of 18.5–23.0 unites (HR = 1.09, 95% confidence interval: 1.06–1.11) 22 . Szentkereszty‐Kovács et al found that the leptin receptor (rs1137101) and brain‐derived neurotrophic factor (rs925946) gene alterations are present in those individuals with psoriasis, suggesting that obesity and psoriasis may share a common genetic background 23 . In response to inflammatory agents such as TNF‐ and IL‐1, leptin levels in adipose tissue increase, mediating obesity‐associated inflammation and playing a role in the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al demonstrated that individuals with a BMI of 30 units had a considerably higher risk of psoriasis than those with a BMI of 18.5–23.0 unites (HR = 1.09, 95% confidence interval: 1.06–1.11) 22 . Szentkereszty‐Kovács et al found that the leptin receptor (rs1137101) and brain‐derived neurotrophic factor (rs925946) gene alterations are present in those individuals with psoriasis, suggesting that obesity and psoriasis may share a common genetic background 23 . In response to inflammatory agents such as TNF‐ and IL‐1, leptin levels in adipose tissue increase, mediating obesity‐associated inflammation and playing a role in the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MR estimations obtained from IVW, weighted median, and MR-Egger regression were not entirely consistent, both IVW and weighted median methods provide evidence suggesting that obesity and psoriasis may share a common genetic background. 23 In response to inflammatory agents such as TNFand IL-1, leptin levels in adipose tissue increase, mediating obesityassociated inflammation and playing a role in the development of psoriasis. Reduced levels of lipocalin in obese psoriasis patients result in a chronic inflammatory state.…”
Section: Heterogeneity and Sensitivity Testmentioning
confidence: 99%
“…Moreover, a population-based case control study among 574 psoriasis subjects of Hungarian origin demonstrated the link between the LEPR gene polymorphism (rs1137101) and obesity prevalence among patients with early disease onset. Multiple single-nucleotide polymorphisms were genotyped in the study, such as ADIPOQ , FTO , PPARG and FTO ; however, no prominent associations were found [ 64 ]. Mitsuyama et al described the significant association between leptin mRNA expression in subcutaneous adipose tissue among psoriatic patients and serum leptin levels, disease severity and obesity [ 65 ].…”
Section: Potential Common Genetic Background Of Obesity Among Psoriat...mentioning
confidence: 99%